Cardiorespiratory and thermal responses to hypercapnia in chickens exposed to CO2 during embryonic development - Rocha, Aline C.G. [UNESP]; Espinha, L.ívia P. [UNESP]; Santos, Kassia M. [UNESP]; Almeida, Ayla R. [UNESP]; Macari, Marcos [UNESP]; Bícego, Kênia C. [UNESP]; Gargaglioni, Luciane H. [UNESP]; da Silva, Glauber S.F. [UNESP] (Elsevier, 2020)
The concentration of CO2 in the environment surrounding the embryo impacts development and may also influence the cardiorespiratory responses after hatching. Therefore, we aimed to evaluate the cardiorespiratory and thermal responses to hypercapnia in chicks that were exposed to CO2 during embryonic development, i.e., incubation. Embryos were incubated without and with a gradual increase in CO2 concentration up to 1 % during the first ten days of incubation. Ten-day-old chicks (males and females) were again acutely exposed to hypercapnia (7 % CO2), or to room air (normocapnia) and pulmonary ventilation, arterial pH and blood gases, arterial blood pressure and heart rate, body temperature (Tb) and oxygen consumption (V⋅O2) were measured. Compared to control animals, male chicks incubated with 1 % CO2 presented an attenuated ventilatory response to hypercapnia (P < 0.05), whereas no difference was found in the hypercapnic ventilatory response in both female chick groups (0 % vs 1 % CO2 incubation). Hypercapnia induced bradycardia in all groups (P < 0.001). The CO2 exposure during incubation did not alter the cardiovascular responses to hypercapnia in post-hatch animals. There were no significant effects of incubation treatment (0 % vs 1 % CO2) or sex in the mean arterial pressure, Tb, and V⋅O2 of animals in normocapnia and hypercapnia. As for the V⋅E/V⋅O2, hypercapnia caused an increase in both groups (P < 0.05), regardless of incubation treatment. In conclusion, among cardiorespiratory and metabolic variables, the ventilatory response to hypercapnia can be attenuated by pre-exposure to 1 % CO2 during embryonic development, especially in male chicks up to 10 days.
Keywords: Arterial pressure and heart rate; Body temperature; Chicken embryo; Chicks; CO2 exposure; Embryonic development; Metabolic rate; Pulmonary ventilation